If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -0.01x + 60 = 0 Reorder the terms: 60 + -0.01x = 0 Solving 60 + -0.01x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-60' to each side of the equation. 60 + -60 + -0.01x = 0 + -60 Combine like terms: 60 + -60 = 0 0 + -0.01x = 0 + -60 -0.01x = 0 + -60 Combine like terms: 0 + -60 = -60 -0.01x = -60 Divide each side by '-0.01'. x = 6000 Simplifying x = 6000
| 3x+-y=-1 | | -3x+3=6-4x | | V+lwh= | | -0.01*x+60=25 | | x/x+7x=7 | | -3c+11A-5a-11c+9c= | | (XxX)+7x=7 | | 1+6x=4x-11 | | x+7x=7 | | fx=x^2+3 | | -0.1*x+60=25 | | 1-2x(5+x)=7 | | (x+4)(x-2)=112 | | 3u^2-75=0 | | Y^2-2y-13=0 | | 2a-5(a+1)=0 | | 3a+2a-a=24 | | x(x+5)-10=x^2-2x+4 | | 2b-7=21 | | h+5h-3-6h=0 | | 3-3n=-27 | | 10-8y+(-13)+12y+8-6y= | | 8(-8)+7y=56 | | 2(2x-6)+2(x+3)=24 | | 12m+9-2m-16=0 | | x+2=-34+5x | | 230=2(3x-5)+2(5x+8) | | 100(4+x)=.75(8+x) | | 59+x=59 | | 7x+2=4x+29 | | 6a+10b-a+b= | | 7=-3x+5x-1 |